2018
DOI: 10.1111/crj.12797
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Krebs von den Lungen‐6 as a predictor of relapse in interstitial pneumonia with anti‐aminoacyl tRNA synthetase antibodies‐positive dermatomyositis

Abstract: These findings suggest that the levels of KL-6 before and after treatment in ARS-DMIP may represent the disease activity of IP, and they may be useful as the predictor of relapse in IP in patients with ARS-DMIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Additionally, some studies showed that the elevated KL-6 level might be a sensitive indicator for the relapse of ILD ( 72 ). We further thought about the reason for the relapse of ILD and concluded that relapse is closely related to ILD progression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some studies showed that the elevated KL-6 level might be a sensitive indicator for the relapse of ILD ( 72 ). We further thought about the reason for the relapse of ILD and concluded that relapse is closely related to ILD progression.…”
Section: Discussionmentioning
confidence: 99%
“…In IIM patients, KL-6 concentrations were found to be significantly higher in patients with ILD compared with those without ILD, and the KL-6 levels were correlated with the ILD course [ 29–31 ]. Furthermore, KL-6 was shown to be a predictive value for the development of ILD [ 32 , 33 ]. To date, few studies have addressed the relationship between serum KL-6 levels and B-lines in IIM-ILD.…”
Section: Discussionmentioning
confidence: 99%